Why Do We Learn English? Investigating the First Year Students’ Motives to Learn English in Aceh - Nurbaiti Nurbaiti; Yunisrina Qismullah Yusuf; Asnawi Muslem; Nurul Inayah (VELES Voices of English Language Education Society, 2023)
Integrative and instrumental motivation both play crucial roles in language learning, so it is crucial for teachers to determine which students' motivations are predominant in a classroom. The motivation of first-year students to learn English was examined in this study. It involved 77 first-year students from the Department of English Education at Universitas Syiah Kuala in Banda Aceh, 56 of whom were females and 21 of whom were males. The research tool utilized to gather the data was a questionnaire. The Attitude/Motivation Test Battery served as its model. The acquired data were analyzed using the Statistical Package for Social Science version 23. The results demonstrated that instrumental motivation's mean score (M=44.18) is higher than integrative motivation's (M=43.38). However, there was little difference (at 0.92 percent ). Therefore, it can be said that these students were driven by both integrative and instrumental motivations. Both of these types of motivations are closely related, and they both function as learning objectives with a lot of value. They benefit by way of the students’ learning outcomes as they become more proficient and successful in the target language.